2002
DOI: 10.1037/0096-3445.131.3.377
|View full text |Cite
|
Sign up to set email alerts
|

When language affects cognition and when it does not: An analysis of grammatical gender and classification.

Abstract: The focus of this work was on the relation between grammatical gender and categorization. In one set of studies, monolingual English-, Spanish-, French-, and German-speaking children and adults assigned male and female voices to inanimate objects. Results from Spanish and French speakers indicated effects of grammatical gender on classification; results from German speakers did not. A connectionist model simulated the contradicting findings. The connectionist networks were also used to investigate which aspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
185
5
9

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(218 citation statements)
references
References 28 publications
16
185
5
9
Order By: Relevance
“…Thereafter, the origins of the color categories in different societies might be constrained by different cultural or environmental needs (Nisbett et al, 2001;Sera et al, 2002;Wierzbicka, 1990Wierzbicka, , 1992, but this question is beyond the scope of the present study.…”
Section: Color Categories 38mentioning
confidence: 88%
“…Thereafter, the origins of the color categories in different societies might be constrained by different cultural or environmental needs (Nisbett et al, 2001;Sera et al, 2002;Wierzbicka, 1990Wierzbicka, , 1992, but this question is beyond the scope of the present study.…”
Section: Color Categories 38mentioning
confidence: 88%
“…One has compared widely differing cultures and languages, such as traditional hunter-gatherer, nomadic or farming communities with native English speakers (Heider & Olivier, 1972;Roberson, Davies & Davidoff, 2000;Roberson, Davidoff, Davies & Shapiro, 2004 while another has compared cultures with similar levels of urbanisation, education, media exposure and lifestyle, whose languages differ in a critical variable -grammatical gender (e.g. Sera et al, 2002;Vigliocco et al 2005;Costa et al, 2003;Segel & Boroditsky, 2011;Bender, Beller & Klauer, 2011;Bassetti, 2007). The latter studies may have the advantage over the former in that differences in performance are less likely to result from other factors that might affect an individual's ability to carry out a task, such as cultural environment.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers investigating the relation between the speakers' conceptual representation of objects and gender grammar have traditionally approached the question in light of whether masculine or feminine images or attributes were projected on objects according to the grammatical gender of the name (e.g., Boroditsky et al, 2003;Konishi, 1993;Ramos & Roberson, 2010;Sera et al, 2002), how grammatical gender affects (implicit or explicit) judgments of similarity of objects by virtue of belonging to the same grammatical gender category (e.g., Vigliocco et al, 2005), or whether grammatical gender class is preserved in speakers' semantic substitution errors during rapid naming (e.g., Kousta et al, 2008;Vigliocco et al, 2004Vigliocco et al, , 2005. In this research, we examined the relation between gender grammar and cognitive processes more directly: We investigated how grammatical gender affected inference about sex-specific biological properties.…”
Section: Discussionmentioning
confidence: 99%
“…German speakers rated the noun meaning "moon" (which is masculine in German, i.e., der [MASC] Mond, and feminine in Spanish, i.e., la [FEM] luna) higher in masculinity than the word for "sun" (which is feminine in German, i.e., die [FEM] Sonne, and masculine in Spanish, el [MASC] sol), whereas Spanish speakers showed the reverse pattern. Sera and colleagues (Sera, Berge, & del Castillo Pintado, 1994;Sera et al, 2002) asked Spanish and French speakers to assign either a female or a male voice to artifact objects and reported that the judgments tended to agree with the grammatical gender of the objects (see also Boroditsky, Schmidt, & Phillips, 2003;Flaherty, 2001;Ramos & Roberson, 2010). Influence of grammatical gender has been identified in tasks that do not involve explicit judgements as well (e.g., Kousta, Vinson, & Vigliocco, 2008;Vigliocco & Franck, 2001;Vigliocco, Vinson, Indefrey, Levelt, & Hellwig, 2004;Vigliocco et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation